Frequency‐Resolved Reciprocal‐Space Mapping of Visible Spontaneous Emission from 3D Photonic Crystals. Issue 9 (25th June 2014) - Frölich, Andreas; Fischer, Joachim; Wolff, Christian; Busch, Kurt; Wegener, Martin
<x xml:space="preserve">Abstract</x> Information on propagating and evanescent Bloch modes as well as on remaining disorder is provided by experiments on titania woodpile photonic crystals with a complete three‐dimensional photonic bandgap at visible wavelengths. Such frequency‐resolved reciprocal‐space mapping of visible spontaneous emission from 3D photonic crystals is analogous to angle‐resolved photoemission spectroscopy (ARPES) on ordinary crystals. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>